Serial order learning of subliminal visual stimuli: evidence of multistage learning - Kido, Kaede; Makioka, Shogo (Frontiers in Psychology, 2015)
It is well-known that statistical learning of visual symbol sequences occurs implicitly (Kim et al., 2009). Here, we examined whether people can learn the serial order of the visual symbols when they cannot perceive them. During the familiarization phase, triplets or quadruplets of novel symbols were presented to one of the eyes under continuous flash suppression (CFS). Perception of the symbols was completely suppressed by the flash patterns presented to the other eye (binocular rivalry). In the test phase, the detection latency was faster for the symbols located later in the triplets or the quadruplets. These results indicate that serial order learning occurs even when the participants cannot perceive the stimuli. We also found that the detection became slower for the last item of the triplets or the quadruplets. This phenomenon occurred only when the participants were familiarized to the symbols under CFS, suggesting that the following symbols interfered with the processing for the target symbol when conscious perception was suppressed. We further examined the nature of the interference, and found that the interference occurred only when the following symbol was not fixed. This result suggests that serial order learning under binocular rivalry is restricted to the fixed order sequence. Statistical learning for the transition probability of the symbols might not occur when participants cannot perceive the symbols. We confirmed this hypothesis by conducting another experiment in which transition probability of the symbol sequence was manipulated.